Hubungan Diabetes Melitus Tipe 2 dengan Penyakit Ginjal Kronis: Tinjauan Literatur: The Relationship Between Type 2 Diabetes Mellitus and Chronic Kidney Disease: A Literature Review - Salsabila, Nuzulia Hikmah; Adhayati, Baety; Selfie, Selfie; Harahap, Alfuu Nur; Sitanggang, Ervina Julien; Prameswari, Yuda Nabella (Journal of Health and Physical, 2026)
Type 2 diabetes mellitus is a major global health problem and one of the leading causes of chronic kidney disease. Chronic hyperglycemia in diabetes plays a crucial role in the development of kidney damage, which may progress to end-stage renal disease if not properly managed. This review aims to explore the relationship between type 2 diabetes mellitus and chronic kidney disease, focusing on underlying pathophysiological mechanisms and clinical implications. A narrative review approach was conducted using literature from PubMed, ScienceDirect, and Google Scholar published between 2016 and 2026. The findings indicate that persistent hyperglycemia contributes to kidney damage through multiple interconnected mechanisms, including oxidative stress, inflammation, and fibrosis. These processes lead to structural and functional alterations in the kidney, such as glomerular dysfunction, declining glomerular filtration rate, and accumulation of metabolic waste products. Furthermore, the coexistence of diabetes and chronic kidney disease is associated with a higher risk of systemic complications, particularly cardiovascular disease, anemia, and metabolic disturbances, which significantly impact patient outcomes. Overall, type 2 diabetes mellitus and chronic kidney disease have a strong and complex relationship. Effective glycemic control, early detection, and comprehensive monitoring of kidney function are essential strategies to prevent disease progression and reduce the burden of complications, highlighting the importance of integrated management in patients with diabetes.